Asbestos exposure and haematological malignancies: a Danish cohort study - Würtz, Else Toft (Eur J Epidemiol, 2020)
Environmental asbestos exposure and occupational asbestos exposure increase the risk of several types of cancer, but the role of such exposures for haematological malignancies remains controversial. We aimed to examine the risk of haematological malignancies: first, in subjects exposed early in life, independently of any occupational exposure occurring later; second, in subjects exposed occupationally. We established an environmentally exposed cohort from four schools located near the only former asbestos cement production plant in Denmark. We identified nearly all pupils in the seventh grade and created an age and sex-matched 1:9 reference cohort from the Danish Central Population Register. Participants were born 1940–1970 and followed up in national registers until the end of 2015. Occupational asbestos exposure was assessed for all participants using two different job exposure matrices. The school cohort included 12,111 participants (49.7% girls) and the reference cohort 108,987 participants. Eight subgroups of haematological malignancy were identified in the Danish Cancer Registry. These cases were analysed for combined overall haematological malignancy, a combined subgroup of lymphomas and a combined subgroup of leukaemias. The data were analysed using Cox regression (hazard ratios (HR)) including other cancers and death as competing risks. Haematological malignancy was identified in 1125 participants. The median follow-up was 49.3 years (0.1–63.4). Early environmental asbestos exposure was not associated with an increased risk of haematological malignancy. Long-term occupational asbestos exposure was associated with overall haematological malignancy (HR 1.69, 95% CI 1.04–2.73); in particular for the leukaemia subgroup (HR 2.14, 95% CI 1.19–3.84). This large follow-up study suggests that long-term occupational asbestos exposure is associated with increased leukaemia risk. However, further studies are needed to confirm these observations. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10654-020-00609-4) contains supplementary material, which is available to authorized users.